Neonatal iliopsoas abscess presenting with transient cyanosis of a single extremity: a case report and review of the literature - Akın, Mustafa Şenol; Ağaçkıran, Damla; Ünal, Emre; Yavuz, Özlem Özkale; Yiğit, Şule (The Turkish Journal of Pediatrics, 2020)
A newborn baby with an unusual complaint of transient left leg cyanosis during crying, who was diagnosed with a iliopsoas abscess is presented. Newborn cases diagnosed with an iliopsoas abscess in the English literature are summarized and differences in clinical presentations are discussed.
Keywords: iliopsoas abscess; newborn; transient single extremity cyanosis